Laparoscopy-Assisted Swenson Pull-Through in Hirschsprung Disease: Experiences in Dhaka Medical College and Hospital (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Hirschsprung disease (HD) is a congenital disorder characterized by absence of ganglion cells in the distal bowel. Minimally invasive approaches such as laparoscopy-assisted pull-through have gained popularity due to better visualization and reduced morbidity.Objective: To evaluate the outcomes of laparoscopy-assisted Swenson pull-through in children with HD.Methods: This prospective study included 16 patients aged 1–7 years who underwent laparoscopy-assisted Swenson pull-through. All patients had a prior transverse colostomy. Operative time, postoperative outcomes and complications were analyzed.Results: The median age was 3.5 years, with 6 females and 10 males. Operative time ranged from 90 to 130 minutes. Oral feeding was initiated on postoperative day (POD) 1–2. Complications included constipation (n=1), enterocolitis (n=1), abdominal distension (n=1), urinary retention (n=1), wound infection occurred in(n=1) after laparoscopy and (n=2) after gut closure. All complications were managed conservatively. One patient required re-catheterization due to urinary retention after laparoscopy. Hospital stays ranged from 5 to 7 days. No mortality was observed.Conclusion:  Laparoscopy-assisted Swenson pull-through is a safe and effective procedure for HD with low complication rates and excellent continence outcomes.Journal of Paediatric Surgeons of Bangladesh (2025) Vol. 16 (1 & 2): 4-7